Design and analysis of repairs for fibre metal composites - Tan, Ambrose Yong Xiang. (2011)
GLARE is a material that has recently gained wide commercial approval with its use on the Airbus A380 fuselage. A project was undertaken, following prior work by Tan J.H. (2010), to gain progress towards an eventual aim of a repair scheme for GLARE, supported by FEM analysis and physical testing. Tan determined the type of repair to be used (a stepped-lap bonded repair), and the following report outlines the results of the project with regards to FEM analysis, machining and physical testing. The FEM analysis qualitatively compared two bond step lengths and five different adhesive “geometries” at highly-stressed areas in the bond line, while the physical testing compared the step lengths. The “geometries” suggested that some excess overlap of adhesive beyond the bond line could be desirable, while the step lengths were found to have little or no effect on stress loading that could be withstood, and the repair itself was able to safely withstand flying conditions. A certain consistent failure behaviour was also observed during physical testing involving fracture in an unexpected location. Experience was also gained in this project with machining GLARE to a quality without delamination, building on Tan’s prior unsuccessful experience, though this area still needs improvement. Based on the results from the various project components (FEM, machining and physical testing), possible areas for continuing development towards a repair scheme include an expansion of FEM, an exploration of clamping options during machining, and investigation of step thickness, surface preparation and adhesive types.